Pengembangan Media Interaktif Berdiferensiasi PaSiBaTer untuk Menguatkan Karakter Kepedulian Siswa Kelas 5 Sekolah Dasar - Purnamasari, Yuli; Trisnantari, Hikmah Eva; Setiani, Rahyu (Universitas Nusantara PGRI Kediri, 2024)
Pancasila Education learning practices have not been able to form character and accommodate the learning needs of all students. Technology optimisation is needed to support learning. Through differentiated interactive media PaSiBaTer, an acronym for pairing cards, watching videos, reading reading materials and applying Pancasila values is expected to improve the caring character of grade V students. This type of development research (R & D) adopts the steps of Borg and Gall. The research stages include: 1) needs analysis and planning; 2) media development, validation, revision; 3) implementation with small group and field trials; 4) measuring effectiveness. Media expert validation for display 82.5; video 84.7; reading material 84.7 with very valid criteria. Material expert validation score 97.5 with very valid criteria. The results of learning observations show the criteria for media practicality are very high. The effectiveness of the media is proven by the results of the SPSS 29 t-test, student character observation data before and after using the media with a significance value of <0.001. There is a significant difference between before and after the use of media to improve students' caring character.